ATORVASTATIN IN ACUTE AND CHRONIC KINDS OF ISCHEMIC HEART DISEASE - V. E. Oleynikov; A. A. Khromova; L. I. Gusakovskaya; N. V. Sergatskaya; E. M. Romanovskaya (Российский кардиологический журнал, 2015)
The review focuses on clinical trials data demonstrating a possibility of effective statin therapy of acute and chronic ischemic heart disease courses. The analysis of maximal dosages of atorvastatin application provided, its early prescription in first 24-96 hours after acute cardiovascular event and in preparing for revascularization with the aim to minimize the risk of adverse effects, death and to improve prognosis. The positive effect of atorvastatin is taken into consideration, mediated by not only its hypolipidemic effect, but a range of pleiotropic effects. The analysis is provided of the data on prevalence and severity of side effects in patients receiving statins.